A Juridical Review of the Non-fulfilment of the Applicant's Age Prerequisite for Child Adoption (Analysis of Supreme Court Decision Number 777 K/Ag/2019): Tinjauan Yuridis Atas Tidak Terpenuhinya Prasyarat Usia Pemohon Dalam Pengangkatan Anak (Analisis Putusan Mahkamah Agung Nomor 777 K/Ag/2019) - M. Yunus, Fakhrurrazi; Eriyanti, Nahara; Fathia, Izza Alta (Prodi Hukum Keluarga Fakultas Syariah dan Hukum UIN Ar-Raniry, 2021)
Government Regulation Number 54 of 2007 concerning the Implementation of Child Adoption explains that the age of prospective adoptive parents is at least 30 (thirty) years old and the highest is 55 (fifty five) years. In the Determination of the Banda Aceh Syar'iyah Court Number 120/Pdt.P/2019 it is stated that a single parent who wants to adopt a child is 59 years old, which according to applicable legal provisions does not meet the requirements or has passed the age limit in the requirements for child adoption. In this case, the Banda Aceh Syar'iyah Court rejected the Petitioner's application, then the Petitioner submitted an application to the cassation level, so that the Supreme Court's decision Number 777 K/Ag/2019 was granted. This study aims to explain the legal considerations by the judges of the Supreme Court in granting Decision Number 777 K/Ag/2019 concerning Child Adoption, to explain the juridical review of Decision Number 777 K/Ag/2019 regarding the cancellation of the first-degree determination. The research method that the author uses is a qualitative descriptive analysis, which consists of primary data materials and secondary data. The results of the study explained that the Supreme Court granted the appeal by using clear legal arguments that were against the legislation. The panel of judges of the Supreme Court granted the request by looking at the advantages and benefits for the adopted child who is the nephew of the single parent. Thus, there was jurisprudence used by judges for the case of Decision Number 777 K/Ag/2019 which is a source of material law. The Supreme Court has issued its decision with legal considerations, the rule of law may be set aside. Juridically, the decision of the Supreme Court is in accordance with the rules in force in Indonesia. With this decision, it can be used as jurisprudence for further judges to handle the same case.